2022
DOI: 10.52380/ijpes.2022.9.1.559
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Nomophobia and Depression, Anxiety and Stress Levels of University Students

Abstract: In today's world, smartphones are an indispensable part of people's daily lives because smartphones facilitate daily routines. However, problematic or excessive use of smartphones can cause some psychological problems. Nomophobia is considered as one of the psychological problems caused by excessive use of smartphones. Nomophobia is referred to as modern age phobia and refers to irrational fears and anxieties of a person who cannot access or communicate with their mobile phone. Therefore, this study examines t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…As for the direct effect, our ndings expand the existing knowledge by providing further support for the positive association between nomophobia and depression, anxiety and stress. In agreement with our results, Tolan and Karahan [10] and Kubrusly et al [57] found a positive correlation between higher nomophobia scores and more severe depression, anxiety, and stress symptoms as assessed by the DASS scale among university students [10,57]. In many studies, nomophobia has been associated with both depression and stress [7,58,59].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As for the direct effect, our ndings expand the existing knowledge by providing further support for the positive association between nomophobia and depression, anxiety and stress. In agreement with our results, Tolan and Karahan [10] and Kubrusly et al [57] found a positive correlation between higher nomophobia scores and more severe depression, anxiety, and stress symptoms as assessed by the DASS scale among university students [10,57]. In many studies, nomophobia has been associated with both depression and stress [7,58,59].…”
Section: Discussionsupporting
confidence: 91%
“…Nomophobia is considered a frequent and emerging problem among university students worldwide [2][3][4][5], and has potential negative impact on their mental health and well-being [2,[6][7][8][9]. Some studies have shown potential association between nomophobia and negative mental health (anxiety, stress and depression) [10][11][12]. For instance, Tolan and Karahan [10], discovered a positive association between university students' levels of nomophobia and their levels of depression, anxiety, and stress, implying that nomophobia was related to poorer mental health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have revealed that levels of depression and anxiety are significant indicators of the nomophobia score among university students. 52 , 53 In a study conducted by Kim et al, students frequently used their phones for extended periods to counteract the negative impacts of depression. 54 According to Green et al, individuals who are addicted to using their smartphones excessively are more likely to experience depression, which exposes them to psychosocial distress.…”
Section: Discussionmentioning
confidence: 99%
“…7 Tolan et al, studied the relationship between the nomophobia levels of university students and their Depression-Anxiety-Stress Levels using Depression Anxiety and Stress Scale (DASS-42) and found a positive correlation between nomophobia and depression-anxiety-stress levels. 8 The prevalence of nomophobia is increasing among the youngster which is an alarming condition that needs to be addressed. Dixit et al 2009 reported that about 73% of students kept their mobile phones for 24 × 7 hr and 20% of students stressed when they do not have their mobile phones or their mobile batteries is drained.…”
mentioning
confidence: 99%